Last updated at March 11, 2017 by Teachoo

Transcript

Example 13 Solve tan–1 2x + tan–1 3x = π/4 We know that tan–1 x + tan–1 y = tan–1 ((𝐱 + 𝐲)/(𝟏 − 𝐱𝐲)) tan-1 2x + tan 3x = tan–1 ((2x + 3x)/(1 − 2x × 3x)) = tan–1 (5x/(1 − 6x2)) Now, given tan–1 2x + tan–1 3x = π/4 tan–1 (5x/(1 − 6x2)) = π/4 5x/(1 − 6x2) = tan π/4 5x/(1− 6x2) = 1 5x = 1 × (1 – 6x2) 5x = 1 – 6x2 6x2 + 5x – 1 = 0 6x2 + 6x – x – 1 = 0 6x(x + 1 ) – 1 (x – 1) = 0 (6x – 1) (x + 1) = 0 ∴ 6x – 1 = 0 or x + 1 = 0 x = 1/6 or x = −1

Chapter 2 Class 12 Inverse Trigonometric Functions

Ex 2.1, 5
Important

Ex 2.1, 8 Important

Ex 2.1, 12 Important

Ex 2.1, 14 Important

Example 5 Important

Example 8 Important

Ex 2.2, 12 Important

Ex 2.2, 15 Important

Ex 2.2, 19 Important

Ex 2.2, 21 Important

Example 10 Important

Example 12 Important

Example 13 Important You are here

Misc. 2 Important

Misc. 7 Important

Misc. 10 Important

Misc. 11 Important

Misc 12 Important

Misc. 17 Important

Class 12

Important Question for exams Class 12

- Chapter 1 Class 12 Relation and Functions
- Chapter 2 Class 12 Inverse Trigonometric Functions
- Chapter 3 Class 12 Matrices
- Chapter 4 Class 12 Determinants
- Chapter 5 Class 12 Continuity and Differentiability
- Chapter 6 Class 12 Application of Derivatives
- Chapter 7 Class 12 Integrals
- Chapter 8 Class 12 Application of Integrals
- Chapter 9 Class 12 Differential Equations
- Chapter 10 Class 12 Vector Algebra
- Chapter 11 Class 12 Three Dimensional Geometry
- Chapter 12 Class 12 Linear Programming
- Chapter 13 Class 12 Probability

About the Author

Davneet Singh

Davneet Singh is a graduate from Indian Institute of Technology, Kanpur. He has been teaching from the past 9 years. He provides courses for Maths and Science at Teachoo.